The cascade effect of collaborative innovation in infrastructure project networks - Zhang, Ruixue; Xue, Xiaolong; Zhang, Yuanxin (Journal of Civil Engineering and Management, 2021)
As infrastructure projects get larger and more complex, innovation, which is highly dependent on collaboration and interactions among stakeholders, is critical to meet the challenges. Nevertheless, the existing literature is lacking in terms of studies into the spread of cooperative behaviors in infrastructure project innovations, on which project success is highly contingent. Hence, based on network science theories, this study aims to shed light on the cascade processes of cooperative behaviors in the evolution of collaborative innovations within infrastructure project networks and the impact of various network structures on the cascade effect. The results indicate that the number of initial innovation adopters is positively correlated with the role that the initial adopters play and the cascade effect of collaborative innovation on infrastructure projects. It is also shown that the cascade effect of collaborative innovations is contingent on project network structures. Furthermore, the results also suggest that network connection is positively correlated with cascade speed, scale, and time to reach a stable state. This study is the first to explore the cascade effect of stakeholders’ interactions vis-a-vis collaborative innovation in infrastructure projects. The findings could assist policy-makers and project managers in taking appropriate measures to encourage innovation in infrastructure projects.